Determinants of earnings quality: the role of the audit committee as a moderator - Nanda Oktavia Simbolon; Christin Natalia Sitorus (Jurnal Akademi Akuntansi)
Purpose: This research aims to examine and analyze the influence of capital structure, liquidity, profit growth, company size, and profitability simultaneously and partially on profit quality and audit committees in companies in the consumer cyclical industrial sector listed on the Indonesia Stock Exchange for the 2021 - 2022 period.